Airfield and Highway Pavements 2019. selected papers from the International Airfield and Highway Pavements Conference 2019, July 21-24, 2019, Chicago, Illinois - Al-Qadi, Imad L.; Ozer, Hasan; Loizos, Andreas; Murrell, Scott (American Society of Civil Engineers, 2019)
Contains 45 peer-reviewed papers on innovation and sustainability of airfield and highway pavements. Topics include: construction quality monitoring of highway pavements; innovations in highway pavement design; sustainable materials; pavements and the environment; life-cycle methods for pavement assessment; airfield pavement design technology and specifications; modeling of airfield pavements; use of accelerated loading systems for airfield pavements; and airfield pavement condition evaluation. This proceedings will be of interest to transportation infrastructure researchers, consultants, designers, project/construction managers, and contractors from around the world.